1997
DOI: 10.16995/trac1996_38_54
|View full text |Cite
|
Sign up to set email alerts
|

Samian: Beyond Dating

Abstract: Surprisingly little work has systematically ex.plored whether samian was treated differently from other pottery types in Britain or how it may have been regarded by different cultural and status groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Such a concern with the social and cultural roles of ceramic evidence runs against the grain of traditional economic approaches to Roman pottery (as reviewed by Greene, 2005a,b), and should be seen in the context of other more recent social approaches to Roman pottery (e.g. Willis, 1997;Hawthorne, 1998;Monteil, 2004;Roth, 2007) and finds assemblages (Eckardt, 2002;Cool, 2006;Derks and Roymans, 2006;Hingley and Willis, 2007).…”
Section: Methods and Datamentioning
confidence: 99%
“…Such a concern with the social and cultural roles of ceramic evidence runs against the grain of traditional economic approaches to Roman pottery (as reviewed by Greene, 2005a,b), and should be seen in the context of other more recent social approaches to Roman pottery (e.g. Willis, 1997;Hawthorne, 1998;Monteil, 2004;Roth, 2007) and finds assemblages (Eckardt, 2002;Cool, 2006;Derks and Roymans, 2006;Hingley and Willis, 2007).…”
Section: Methods and Datamentioning
confidence: 99%
“…It seems especially well represented on sites which were important in the Iron Age and maintain centrality after the Conquest. Samian enjoyed a complex relationship with other early imported types, such as GalloBelgic wares, including platters, jars and flagons, with Samian taking over some of the roles of the early types (Willis, 1997(Willis, , 1998. More broadly, these imported wares became part of a repertoire of wheel-turned pottery made in Britain, the potter's wheel being introduced before 100 BC in some parts of eastern England, spreading in a complex fashion over the next 150 years or so.…”
Section: Sourcementioning
confidence: 99%
“…Clarke 1997; Hill 1995). Willis (1997) has identified a number of large groups of unused and near‐complete samian vessels on sites in Britain and demonstrated that they all appear to have been deposited at times of structural or occupational change at settlements and times of site refashioning. The association between ritual activity and the negotiation of structural and landscape change can also apply to the installation of waterfronts.…”
Section: Ritual Symbolism and Waterfront Construction At Londonmentioning
confidence: 99%